A study on the performance of bandpass sampling technique in demodulating fetal doppler ultrasound signals: article - Halim, Mohd Afiq Wildan (2010)
Doppler Ultrasound technology has been widely used in medical field. One of the applications of this signal is to get the information about heart movements to check the sign of abnormalities. Demodulation technique has to be performed to extract information from the Doppler Ultrasound signal. There are few types of demodulation and one of them is bandpass sampling technique. A hardware set-up was arranged to send the data out from the PC. In order to create DUS signal that has the same characteristic as the real raw signal from patient, the signal from PC is mixed with Megahertz signal using a mixer. After the signal has downconverted using bandpass sampling technique, the signal is then analysed to confirm that the correct signal is obtained.